Youth Mobility and Territorial Disparities: An Analysis of Urban and Rural Barcelona. - Delclòs‐Alió, Xavier; Miralles‐Guasch, Carme (Geographical Review, 2019)
Travel behavior of the present generation of youths is being increasingly explored due to their relevance in shaping future accessibility needs and mobility habits. The present study offers an original perspective on this topic by identifying territorial disparities that emerge in youth mobility patterns in rural and urban areas. Unlike most previous research, we propose taking a global view on mobility by analyzing all trip purposes and transportation modes. This is conducted by analyzing a comprehensive mobility survey in the Barcelona Metropolitan Region, which provides data on mobility engagement, trip purposes, modal split, travel times and territorial differences. In general, youngsters account for larger daily travel times than older adults, present a higher attachment to public transportation and walk less on a daily basis. These differences are enhanced in rural territories, where while older adults overcome accessibility issues with higher use of the private vehicle, youngsters are more likely to invest larger travel times on transit.